Abstract 18 Developing a Potency Assay for Cord Tissue MSCs. (6th September 2022) - Parrott, Roberta; Noldner, Pamela; Xu, Li; Filiano, Anthony; Shaz, Beth; Kurtzberg, Joanne
Abstract: Introduction: The potency of mesenchymal stromal cells (MSCs) can be assessed by their ability to suppress proliferation of third party stimulated peripheral blood T cells. This correlates with decreased cellular production of IL-2Ra. Objective: We optimized a potency assay for human cord tissue MSCs (hCT-MSC) in clinical trials for subjects with neuroinflammation. Originally, this T cell suppression assay required radioactive tritiated thymidine, rendering the assay difficult to use in a quality control laboratory for product release. Accordingly, we are developing a modified assay that eliminates the tritiated thymidine and instead tests for production of IL-2Rα in harvested supernatants. Methods: The modified assay utilizes freshly thawed hCT-MSCs plated in a 96-well Corning CellBIND plate in Fuji Prime-XV XSFM MSC expansion medium at three concentrations. The hCT-MSCs are incubated 1-6 days at 37°C with humidified 5% CO2 until 80%-100% confluent. At this point, three different, previously qualified, normal control peripheral blood mononuclear cells (PBMCs) are suspended in RPMI 1640 with HEPES medium and 10% fetal bovine serum (FBS) with and without Dynabead (Human T-Activator CD3/CD28). After 4 additional days in culture, 75 µL of supernatant is removed and frozen at –80°C for future assaying of IL-10, TNFα, IFNg, and IL-2Ra using the Ella (Bio-Techne). IL-2Ra was determined to have the best correlation with the original method of suppression of proliferation. In the original radioactivity method after 4 days, the cells were pulsed with tritiated thymidine, harvested 6-10 hours after pulsing, and counted in the MicroBeta2 counter. Results: Seventeen hCT-MSC lines were then tested in both assays. The passing criteria was >70% suppression in the radioactivity assays or >70% decrease in IL-2Ra production in the Ella assay. All 17 hCT-MSC lots passed in the radioactivity-based assay, while 16/17 lines passed using the IL-2Rα assay. Subsequently, the number of PBMCs plated per well and the number of days the PBMCs were in culture were optimized to maximize production of IL-2Rα. Discussion: We developed a potency assay for MSCs that eliminates the use of radioactive reagents and usable as a release assay in manufacturing of hCT-MSC.